Drug Overdose Prevention: Needs of Healthcare Professionals and First Responders - Armstrong, Gaylene (2019)
Purpose and BackgroundThe Nebraska Department of Health and Human Services (DHHS) partnered with Support and Training for the Evaluation of Programs (STEPs) at the University of Nebraska at Omaha, Grace Abbott School of Social Work, to complete a statewide needs assessment between October 2018 and April 2019. The purpose of this needs assessment was to gauge the capacity of statewide systems in Nebraska to respond to surges or clusters of intentional, unintentional, and unknown drug overdoses, especially in high-burden areas and with a focus on opioids. The hope of the results from this needs assessment is to inform DHHS on the development of incident management for crisis response. The needs assessment included a literature review, quantitative surveys, and qualitative focus groups and interviews. The results of the literature review can be found in the Drug Overdose Prevention Needs Assessment: Promising Practices report submitted by STEPs to DHHS in December of 2018. Please contact DHHS to request access to this report. Participants by RegionSTEPs collected qualitative and quantitative data in each of the six health regions across the state. 247 EMTs and firefighters, and 133 health care professionals responded to quantitative surveys; STEPs conducted 33 focus groups and interviews with healthcare professionals, EMTs and firefighters, and law enforcement. Below is a representation of the percentage of overall responses from each health region with bluetext indicating the percentage of focus group and interview participants and goldtext indicating the percentage of quantitative survey responses. (For example, 21% of all focus groups and interviews were conducted in Region 1, and 8% of all survey responses were from Region 1.